A biometric-based authentication system for e-security - Tharuka, Garagoda Arachchige Wageesha Nirmal (Nanyang Technological University, 2024)
The report explores into the realm of cybersecurity and authentication methods, particularly focusing on the implementation of biometric authentication systems, specifically static biometrics. It provides an in-depth analysis of technical security measures and human and organisational factors crucial for fortifying digital infrastructures against potential threats.